The Differences of Student Independence Based on the Status of High School in Jambi Province - Siti Hadijah; Sarwi Sarwi; Masturi Masturi (International Conference on Science, Education, and Technology, 2021)
This study aims to determine the differences in self-afficacy of students in Jambi province. The research sample was 106 students from 4 high schools. Sample selection using purposive sampling technique. The instrument used is a self-afficacy questionnaire with a Likert scale type. Analysis of the data used for the prerequisite test is the normality test, to test the hypothesis using the Independent Sample T-test to determine whether or not there is a difference. Based on the results of this study, out of 5 comparisons there is 1 comparison whose results show differences in self-afficacy. The results obtained are the value of T table = 2.039 > Tcount = 1.673 with a significant level of 0.05, so that there are differences in self-afficacy in SMA X and SMA Y. Whether or not there is a difference is influenced by several factors, such as the area they live in, school status, and student background. Self-afficacy refers to a person's belief about the ability to learn or take action at a certain level.